High Redox Status as the Basis for Heavy Metal Tolerance of Sesuvium portulacastrum L. Inhabiting Contaminated Soil in Jeddah, Saudi Arabia - Emad A. Alsherif; Turki M. Al-Shaikh; Omar Almaghrabi; Hamada AbdElgawad (MDPI AG, 2021)
Because sewage sludge is contaminated with heavy metals, its disposal in the soil may pose risks to the ecosystem. Thus, heavy metal remediation is necessary to reduce the associated risks. The goal of this research is to introduce a heavy metal resistant species and to assess its phytoremediation, oxidative damage markers and stress tolerance mechanisms. To this end, field research was done to compare the vegetation of polluted sites to that of a healthy site. We found 42 plant species identified in the study, Sesuvium portulacastrum L. was chosen because of its high relative density (10.3) and maximum frequency (100 percent) in the most contaminated areas. In particular, S. portulacastrum plants were characterized by strong Cu, Ni, and As uptake. At the organ level, to control growth reduction and oxidase damage, particularly in roots, increased detoxification (e.g., metallothionein, phytochelatins) and antioxidants mechanisms (e.g., tocopherols, glutathione, peroxidases). On the other hand, flavonoids content and the activity of glutathione-S transferase, glutathione reductase and dehydroascorbate reductase were increased manly in the shoots. These biochemical markers can be applied to select tolerance plant species grown under complex heavy metal contamination. Our findings also introduced S. portulacastrum to reduce soil contamination0associated risks, making the land resource available for agricultural production.